The accuration of parallel radiograph technique in measurement of alveolar crest resorption on removable orthodontic treatment - Setyani, Aisa Nirmala; Sam, Belly; Syiarudin, Elih (Padjadjaran Journal of Dentistry, 2014)
Introduction: The parallel radiograph technique produce the accurate measurement so that it can be used to detect the small changing in the hard tissue. In the orthodontic treatment, the force which is given when the activation make the resorption of alveolar crest happen. The purpose of this study is to obtain data of the photo using radiograph periapikal parallel technique and the resorption of alveolar crest in orthodontic treatment during 3 weeks after the first activation. Methods: This quantitative descriptive study used the accidental sampling methode. The data was collected by using parallel radiograpy photo when the first aktivation of coil component in the removable orthodontic patient and 3 weeks after it. Then it was digitilized using the camera and proceeded by Easydent program. After that the tooth lenght of the first and second photos was counted. While to measure the a lveolar crest used the matematic proyection. Results: The result showed p>0,05 which meaned there was no significant differences of the tooth lenght between the first and second photos. The resorption of alveolar crest in this removable orthodontic treatment after the force was given during 3 weeks, was 0, 69899 mm. Conclusion: The parallel radiography technique which is used in this study could be used in the measurement of such condition with reccurent time and the accurate result, and the resorption of the alveolar crest in the insisive central mandibule effected by removable orthodontic treatment was in normal range.